1776 [videorecording (DVD)] - Hunt, Peter H.; Daniels, William, 1927-; Da Silva, Howard, 1909-1986; Howard, Ken, 1944-2016; Danner, Blythe; Vestoff, Virginia; Edwards, Sherman; Ostrow, Stuart, 1932- (Columbia TriStar Home Entertainment, 2002)
1776 is a delightful musical celebration of the founding of The United States of America. The story centers around the familiar historical characters as they organize a movement for independence from Mother England. All events lead up to that most significant date, July 4, 1776, when the Declaration of Independence was signed. This is the DVD "restored" version which runs ca. 166 minutes -- longer than the theatrical release cut, yet shorter than the laserdisc "restored" version.